Interprofessional Collaborative Education: Undergraduate Nursing and Social Work Students Preparation for Safeguarding Children Practice - Morgan, Llewellyn
Morgan & Spargo (2017) identify that nurses feel underprepared by their undergraduate education to work in the field of safeguarding children. Furthermore, Bennett, Plint, & Clifford (2005), Pabiś, Wrońska, Ślusarska, & Cuber (2010) also report particularly for children’s nurses that they have limited exposure to safeguarding during their pre-registration education. Morgan & Spargo (2017) further identify that this maybe as a result of qualified practitioner reluctance to allow those students to participate in safeguarding children practice.Thus, as educationalists we need to explore ways to address this, and approach safeguarding education differently. Murphy (2004) and Munro (2008) suggest that collaborative and interprofessional education should also feature within safeguarding education. Logan, Quiñones, & Sunderland (2015), Houston & Thompson (2017) and Wood & Perlman (2017) suggest that students learn and are able to apply information when it is based upon realistic situations. They extol the benefits of authentic learning which allow for students to develop transferrable skills which they can feed forward into future clinical practice.This presentation reports on the implementation of a pilot project to address preparation for safeguarding work with final year undergraduate children’s nursing students and student social workers at one Higher Education Institute located in South West Wales in the UK. The authentic learning modality adopts recognized safeguarding procedures (in this case the All Wales Child Protection Procedures (2008)) to guide the participatory learning event using simulation. This will utilize a “professional strategy discussion” alongside a simulated “initial child protection case conference”. The rationale for selection is that anecdotally students often self-report that these two activities cause them the most anxiety because of rationalising their decision-making processes when questioned, and they lack understanding of these process requirements.A total of 70 students (mixed groups of student children’s nurses and student social workers) participated in this learning event. Mixed groups were utilized, to allow for discussion and ideas to be formulated and explored, based upon different role viewpoints. These mixed groups were facilitated by professionals and academics, with relevant professional expertise, in order to effectively manage discussions and address individual participant concerns. The formal evaluation of this initial pilot learning event forms the content of the presentation for this conference. This will also feed forward to future and further planned ongoing research.